Laser induced Breakdown Spectroscopy for new product development in mining industry. (2021) - Bellie, Viswanath; Gokulraju, R.; Rajasekar, C.; Vinoth, S.; Mohankumar, V.; Gunapriya, B.
Abstract: Material identification and elemental analysis plays a major role in mining research. Geological prospecting gives us an insight into possible areas where minerals could be located. Costs incurred on mineral identification are high and at times lead to failure in identification. Hence, a deeper and accurate study is required to identify the elements available. Many tools and techniques have been used like XRD, XRF, and Raman Spectroscopy etc. A new and versatile technique for qualitative and quantitative material analysis is laser induced breakdown spectroscopy (LIBS) used in developed countries. This study aims at developing a new product, a low-cost portable, gross weight 3 kg, hand held LIBS tool for instant element identification with provision for mobile access of emission spectra and online system monitoring using cloud. The device is to be eco-friendly and a solar power backup will be provided. The challenges of miniaturization, portability, indigenization, cost and accuracy of data obtained will be addressed in this project.